An Example of Innovative Teaching: How to Start and Run a Financial Investment Company from a Finance and Accounting Perspective? - Kohli, Raj K.; Pant, Anurag (Archives of Business Research, 2022)
An example of an account of practice is presented in this paper. Such action learning methods are highly desired in the attempts to make our courses experiential. Specifically, this project is a new idea for applying and enhancing an undergraduate Capstone Finance course (F444) as well as for a Graduate Financial Management Course (F542). This project guides students to start a new investment company in the State of Indiana and then run it during the semester. As part of an advanced financial course, students maintain and grow an actual portfolio of securities, called Student Managed Investment Fund (SMIF). Hands-on training of this kind is expected to lead to stronger learning of concepts, better application of theories, and significantly more student satisfaction.